2014
DOI: 10.1002/cmdc.201402035
|View full text |Cite
|
Sign up to set email alerts
|

Gyrase ATPase Domain as an Antitubercular Drug Discovery Platform: Structure‐Based Design and Lead Optimization of Nitrothiazolyl Carboxamide Analogues

Abstract: In this study, we explored the pharmaceutically underexploited mycobacterial gyrase ATPase (GyrB) domain as a template for a structure-based virtual screening of our in-house (BITS Pilani) compound collection to discover new inhibitors targeting Mycobacterium tuberculosis (M.tb.) The hit identified was further customized by using a combination of molecular docking and medicinal chemistry strategies to obtain an optimized analogue displaying considerable in vitro enzyme efficacy and bactericidal properties agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…The catalytic subunits (GyrA/ParC) are clinically validated drug targets of the fluoroquinolones, such as moxifloxacin (MXF) (2), while the ATPase subunits (GyrB/ParE) have not been as extensively exploited and may present a new option for treating DR strains of M. tuberculosis (3). Furthermore, several different chemical classes have been described as inhibitors of gyrase B with potent activity against DR bacteria, including M. tuberculosis (4)(5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…The catalytic subunits (GyrA/ParC) are clinically validated drug targets of the fluoroquinolones, such as moxifloxacin (MXF) (2), while the ATPase subunits (GyrB/ParE) have not been as extensively exploited and may present a new option for treating DR strains of M. tuberculosis (3). Furthermore, several different chemical classes have been described as inhibitors of gyrase B with potent activity against DR bacteria, including M. tuberculosis (4)(5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…To provide a structural basis for further inhibitor improvement, compound 12 was subjected to molecular docking calculations using the crystal structure of gyrB ATPase domain of Mycobacterium smegmatis retrieved from Protein Data Bank (PDB ID -4B6C) 22 as template; utilizing a protocol detailed in the experimental section. The compound exhibited good interaction profile in docking studies retaining critical polar and non polar interaction comparable to that of (3,4-dichloro-5-methyl-N-[4-(5-nitro-1,3-thiazol-2-yl)cyclohexyl]-1H-pyrrole-2-carboxamide, a potent gyrB inhibitor [gyrB IC 50 = 0.49 µM], identified from our earlier study 28 with an RMSD of less than 0.5 Å as shown in Figure 2 suggesting the suitability of the identified hit for further structure activity explorations.…”
Section: Resultsmentioning
confidence: 76%
“…All these modification resulted in very potent molecules as shown in Tables 2, 3 and 4. The N-benzyl amino (26)(27)(28)(29)(30), carboxamide (31)(32)(33)(34)(35) was well accommodated as the right hand core than their corresponding sulphonamide analogues (36- A structural insight into the interaction profile of the most potent compound inhibitor from the study compound 27 (Figure 4) showed the molecule to be involved in polar contact with Asn52, a crucial residue of gyrB. Additionally, a cation-π interaction was also observed between the amino group of Arg82 and thiazole of compound.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations